2014
DOI: 10.1249/mss.0b013e3182a44767
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Behavior, and C-reactive Protein in Pregnancy

Abstract: Objectively measured light-intensity physical activity had a protective effect on CRP among women in the second trimester of pregnancy. Findings highlight the need for longitudinal studies of pregnancy physical activity and CRP with careful control for clinical characteristics of the current pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…It appears both groups have elevated cardiovascular disease risk; however, physical activity during pregnancy might modulate this risk in obese women. Our finding is consistent with Hawkins et al who found that physical activity is associated with lower CRP in normal-weight pregnant women (Hawkins et al 2014). Our study extends this work by demonstrating the benefits of physical activity on inflammation also apply to obese pregnant women during late pregnancy- a population at high risk for excessive inflammation during pregnancy and its downstream sequela.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It appears both groups have elevated cardiovascular disease risk; however, physical activity during pregnancy might modulate this risk in obese women. Our finding is consistent with Hawkins et al who found that physical activity is associated with lower CRP in normal-weight pregnant women (Hawkins et al 2014). Our study extends this work by demonstrating the benefits of physical activity on inflammation also apply to obese pregnant women during late pregnancy- a population at high risk for excessive inflammation during pregnancy and its downstream sequela.…”
Section: Discussionsupporting
confidence: 93%
“…The physiological and hormonal changes associated with pregnancy magnify this risk during and after pregnancy by causing an increase in adiposity and insulin resistance (Artal 2015). In pregnant women of normal body weight, physical activity reduces inflammation (Hawkins et al 2014; Wang et al 2014), as well as improves maternal insulin sensitivity (Hopkins and Artal 2013). In obese pregnant women, physical activity may decrease insulin resistance (van Poppel et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Women were also asked if they were ‘mostly sitting’ during their usual daily activities.PoorEvenson, et al (2011) [11]USA359Cross-sectionalPregnant women ≥16 years.ActiGraph accelerometer.Objective.Activities expending <100 counts per minute.IntermediateGollenberg, et al (2010) [36]USA1006CohortLatina ethnicity, age 16–40 years old, singleton pregnancy, and no prior participation in the study.Modified version of the Kaiser Physical Activity Survey (KPAS).Non-objective.Hours spent TV watching per day and frequency of sitting at work.IntermediateGradmark, et al (2011) [47]Sweden101Cross-sectionalNormal weight and overweight women without diabetes were studied.Actiheart monitor.Objective.Epochs with valid heart rate data and zero accelerometry counts/min.IntermediateHawkins, et al (2014 Im.) [48]USA260Randomized controlled trialWomen in their first trimester of pregnancy, between 16 and 40 years old, and at high risk for GDM.Pregnancy Physical Activity Questionnaire (PPAQ).Non-objective.The amount of time spent watching TV or videos, or sitting or standing at home, work, or during transportation.GoodHawkins, et al (2014 PA) [10]USA294Cross-sectionalWomen in the 2003–2006 NHANES study cycles who self-reported currently being pregnant, were 16 year or older, and who had available data on C reactive protein, physical activity, and SB.ActiGraph accelerometer.Objective.Activities expending <100 counts per minute.IntermediateHayes, et al (2014) [49]UK183Randomized controlled trialAll obese (BMI ≥ 30 K/m 2 ) pregnant women.- Acti-Graph accelerometer.- Objective.- Accelerometry: any minute with ≤100 counts/min.Good- Recent Physical Activity Questionnaire (RPAQ).- Non-objective.- RPAQ, minutes spent on activities <1.5 MET.Hegaard, et al (2010) [32]Denmark4558CohortDanish-speaking pregnant women.Self-reported questionnaires.Non-objective.Those who chose “mostly sitting” to describe most correctly her level of leisuretime activity.IntermediateHegaard, et al (2011) [35]Denmark4718…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies 1 declared that sleeping was included [9], 2 stated that sleep time was not considered [8, 11], and the rest did not declare anything regarding sleep [10, 12, 44]. Meanwhile the study which assessed using a questionnaire found that women spent 2.4 h per day watching television and the mean of total sitting time was 8.6 h per day [42] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation